IMPLEMENTASI DIGITAL DASHBOARD UNTUK MENGONTROL WILAYAH RT/RW - Yulhendri Yulhendri; Holder Simorangkir; Faridho Faridho; Dendy Kurniawan (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
Kelurahan Kemanggisan is an institution under kecamatan Palmerah that regulates the rules and administration of RT and RW. Kelurahan Kemanggisan requires media to monitor the activities and administration carried out by residents to RT, RT to RW or vice versa. To determine the right type of media, the authors conducted a study. The method applied in the study is a qualitative data collection technique, which data is obtained from the side of kelurahan and residents. From the results of these techniques, the authors then grouped the data for the purpose of analyzing the problem with the fishbone problem analysis technique. The results of the analysis explain, that the main problem is something related to the activities and administration of citizens of RT and RW or vice versa. The data is not recorded in kelurahan Kemanggisan because the recording by RT and RW is still manual, namely by recording on paper. For this reason, the authors propose the right type of media for kelurahan in terms of monitoring is the existence of a digital dashboard. The data source comes from residents, RT and RW through mobile application media that they operate for the purpose of updating activities and administration. Digital dashboard visualizes data in the form of tables, graphs and maps. That way, the results of the visualization make it easier for kelurahan in terms of monitoring, this is indicated by the existence of accurate data sources in terms of residents, RT and RW.